The Acquisition of Computational Thinking through Mentoring: An Exploratory Study - Núria Cervera; Pascual D. Diago; Lara Orcos; Dionisio F. Yáñez (MDPI AG, 2020)
Educational robotics are commonly present in kindergarten and primary school classrooms, particularly Bee-bot. Its ease of use allows the introduction of computer programming to young children in educational contexts from a science, technology, engineering, arts, and mathematics (STEAM) perspective. Despite this rise, there are still few investigations that collect evidence on the effectiveness of robotic interventions. Although mentoring experiences with robotics had been carried out in educational contexts, this work explores their effect on the acquisition of computational thinking skills through mentoring. Participants from the second grade, aged seven through eight years, were exposed to two sessions of robotics with Bee-bot in order to promote hands-on experimentation. The sessions were conducted by nine students of the fourth grade (the mentors), aged 10 to 11 years. A descriptive case-study methodology was employed for the analysis of the mentoring intervention. The effect of the mentoring experience was assessed in terms of motivation and computational thinking skills. Mixed quantitative and qualitative results show two important findings: (i) Mentoring is a powerful tool to be considered for improvement of the motivation and cooperation of students in their teaching-learning process, and (ii) computational thinking skills can be acquired by second-grade students through a mentoring process.